A Novel Target for Diuretic Therapy (Iranian Journal of Kidney Diseases, 2012)
The reabsorption of salt in the distal nephron is predominantly mediated via the thiazide-sensitive sodium chroride cotransporter, NCC (SLC12A3), and the chloride-bicarbonate exchanger pendrin (SLC26A4, PDS), with pendrin working in tandem with the epithelial sodium channel and NCC working by itself. Single deletion of NCC or pendrin in genetically engineered mouse models does not cause salt wasting or excessive diuresis under basal conditions. Both pendrin knockout and NCC knockout mice, however, show signs of volume depletion or develop hypotension during salt restriction. These findings have led investigators to conclude that pendrin and NCC are predominantly active during salt depletion and their contribution to salt reabsorption at baseline conditions is small. We hypothesized that pendrin may compensate for loss of NCC under basal conditions, thereby masking the role that each transporter plays in salt reabsorption. To test this hypothesis, double knockout of pendrin and sodium chloride cotransporter was generated by crossing animals with single deletion for NCC and pendrin. The double-knockout mice show significant salt and fluid wasting, along with severe volume depletion, metabolic alkalosis and prerenal failure under baseline conditions. Volume depletion, metabolic alkalosis and prerenal failure were significantly corrected with salt repletion. We conclude that pendrin plays an essential role in the distal tubule salt reabsorption in the setting of sodium-chloride cotransporter inactivation. We propose that pendrin could be a novel target for a new diuretic that in conjunction with thiazide can be an effective regimen for patients with fluid overload.